Proyecto de Inversión para la creación de una empresa de diseño y logística de eventos empresariales sostenibles dirigido a las PYMES de la ciudad de Pereira. (2013)
The Event Planning is a way to support business longevity and is also a way of caring for the environment. The environmental issues are becoming really important and there are multiple companies that seek to minimize its impact through event planning. To develop the investment project, a research methodology was used that involved market analysis, as well as technical, business and legal design. In order to achieve the objectives of the study, research techniques, such as surveys and its tabulation, were applied. This enabled to know the acceptance that event planning companies have in Pereira. Also, the legal and fiscal requirements were identified and the overall size of the project was determined. The proper size, and needed infrastructure was also discovered. With the admin research, the adequate staff was established: only a manager, a secretary, a consultant and a CPA are needed. The competitive strategies theories of Michael Porter, where the lower cost and differentiation of a business unit makes the products more efficient than those of the competition and provide the buyer with a unique and superior value, were taken into account. The Event Planning sustainability is clearly a differentiating factor and at the same time a business opportunity in the so called Green Economy; which will create a good image for the company and its customers.